VARIASI STRUKTUR ANATOMI DAN KUALITAS SERAT KAYU DENGEN (Dillenia serrata) DALAM SEBATANG POHON - Muthmainnah, Muthmainnah; Asniati, Asniati; Erniwati, Erniwati; Ariyanti, Ariyanti; Hapid, Abdul (Universitas Tanjungpura, 2024)
Dengen (Dillenia serrata) is a type of tree from the Dilleniaceae tribe which is widely distributed in Asia, including Indonesia. This tree is found in many areas of Indonesia, including Sulawesi. This tree grows in areas with an altitude of 80